Meaningful Movement and Literacy Content - Gayla Lohfink; Rick Pappas (The Advocate, 2016)
Links among brain research, movement, and cognition suggest that integrating meaningful movement activities with content can foster elementary students’ engagement in literacy learning. This manuscript describes an action research project of a module for teacher candidates’ incorporation of meaningful movement in elementary classrooms. Activities and their alignment to the English Language Arts standards are described. Evidence of the impact of the module on teacher candidates’ planning reflects that 41% of candidates’ lessons showed intentional movement, specifically by encouraging children to move about the classroom, use body gestures, and rotate physically though centers.